The effect of multiple lightning impulse on the electrical characteristic of an opto - isolator as low voltage protective device [electronic resource] - 191704 Navingdren Maniam; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007